Validity and Responsiveness of the Generic Health-Related Quality of Life Instrument (VetMetrica™) in Cats With Osteoarthritis. Comparison of Vet and Owner Impressions of Quality of Life Impact - Scott, E. Marian; Davies, Vinny; Nolan, Andrea M.; Noble, Cory E.; Dowgray, Nathalie J.; German, Alexander J.; Wiseman-Orr, M. Lesley; Reid, Jacqueline (Frontiers in Veterinary Science, 2021)
Validity is not an inherent property of a measurement scale and so evidence for validity relating to its use for particular purposes, with defined populations and in specified contexts must be accumulated. We have published the development of a web-based, generic health-related quality of life instrument (VetMetrica™) to measure the affective impact of chronic disease in cats and provided evidence for its validity in a mixed population of cats, some of which, according to veterinary judgement, were healthy and others of which were suffering from chronic conditions likely to affect their quality of life, often with multiple co-morbidities present. The first aim of the current study was to demonstrate the construct validity of the VetMetrica™ generic instrument when used with cats suffering from osteoarthritis, by testing the hypothesis that the health-related quality of life profile of cats with different severities of osteoarthritis would differ and by demonstrating convergent validity between the health-related quality of life profile scores and independently quantified vet-assessed pain and quality of life impact scores. The latter involved simple correlation analysis and investigation of the relationship between health-related quality of life domain scores and vet-assessed scores, when adjusted for other potential explanatory variables including number of comorbidities and age. Responsiveness – the ability to detect clinically relevant change - is an essential quality for an evaluative instrument and it also provides evidence for ‘longitudinal validity’. Therefore, a second aim of this study was to demonstrate that changes in health-related quality of life domain scores concurred with the clinician’s impression of change over time in the health status of cats with osteoarthritis, thus providing evidence for the instrument’s responsiveness. Previously, we have reported disagreement between owner and vet impression as to health status in cats in general, but not in relation to any specific disease. Accordingly, the third study aim was to investigate the extent of agreement or disagreement between owner impression of the impact of osteoarthritis on their cats’ quality of life and vet impression of such impact. 51% of cat owners believed their cats to be perfectly healthy despite a clinician diagnosis of osteoarthritis